Impact and Compensation of Electrical-to-Optical Frequency Response on Carrierless Phase Retrieval Receivers - Qi Gao; Hanzi Huang; Zhengxuan Li; Ziyue Liu; Yuanzhe Qu; Yingxiong Song (IEEE Photonics Journal, 2024)
On carrierless phase retrieval (PR) receivers based on direct detection, bandwidth limitation of electrical-to-optical (E/O) conversion at the transmitter side (Tx) distorts the modulated optical signal. In this paper, we propose the Gercheberg-Saxton (GS)-aided and the data-aided estimation method in order to know the complex-valued of E/O channel response in the absence of phase information. Furthermore, we compare four channel estimation schemes based on the mean square error (MSE) between the estimated and preset channel response in numerical simulation, which are generated by combining least mean square (LMS) or least square (LS) with the proposed GS-aided or data-aided methods. In order to compensate the distortion from E/O frequency response, two compensation schemes including pre-equalization processing at the Tx and post-equalization processing at the Rx are implemented and compared by simulations and experiments. In the experiment, we transmit a single-polarization 30GBaud QPSK signal including a training sequence of 2048 symbols to estimate the E/O conversion frequency response over 55-km single-mode fiber (SMF). The received signal is detected by a PR receiver employing different estimation (LMS/LS) and equalization (pre-/post-) schemes to compare their performance. The experimental results demonstrate that all estimation schemes successfully estimate the frequency response in the absence of phase information, and PR employing pre-equalization with GS-aided-LMS estimation exhibits good robustness, resulting in a received optical power improvement of 0.69 dB to achieve 20% forward-error correction (FEC) threshold.